Metachronous lesions in the orbit, retroperitoneum, and pleura of mucosa‐associated lymphoid tissue lymphoma: A case report. Issue 10 (28th July 2022) - Shiono, Ayako; Imai, Hisao; Satou, Tsugumi; Taguchi, Ryo; Takahashi, Naoki; Azuma, Ryuichi; Yamaguchi, Ou; Hashimoto, Kosuke; Naito, Erika; Iemura, Hidetoshi; Miura, Yu; Mouri, Atsuto; et al.
Abstract: Background: Mucosa associated lymphoid tissue (MALT) lymphoma of the orbit is rare, often indolent, but can recur, and spread to extra‐nodal sites. Pleural and retroperitoneum recurrences of MALT lymphoma are rare. Case: A 65‐year‐old man was referred to our hospital due to right pleural effusion and difficulty in breathing. He had a medical history of having undergone surgery for MALT lymphoma of the left orbit. A chest computed tomography (CT) scan showed right pleural thickness, pleural effusion, and a retroperitoneal mass, spreading from the muscular layer to the subcutaneous layer. The thickened pleural lesion was surgically biopsied and diagnosed as a recurrence of MALT lymphoma. Conclusion: Pleural effusion should be carefully examined and monitored for the possibility of recurrence in MALT lymphoma patients.